How research-based theatre is a solution for community engagement and advocacy at regional medical campuses: The Health and Equity through Advocacy, Research, and Theatre (HEART) program (Canadian Medical Education Journal, 2018)
Background: Regional medical campuses are often located in geographic regions that have different populations than the main campus, and are well-positioned to advocate for the health needs of their local community to promote social accountability within the medical school.Methods: At the Niagara Regional Campus of McMaster University, medical students developed a framework which combined research, advocacy, and theatre to advocate for the needs of the local population of the regional campus to which they were assigned. This involved a qualitative study using semi-structured interviews with homeless individuals to explore their experience accessing the healthcare system and using a transformative framework to identify barriers to receiving quality healthcare services. Findings from the qualitative study informed a play script that presented the experiences of homeless individuals in the local health system, which was presented to health sciences learners and practicing health professionals. Participants completed two instruments to examine the utility of this framework.Results: Research-based theatre was a useful intervention to educate current and future health professionals about the challenges faced by homeless individuals in the region. Participants from both shows felt the framework of research-based theatre was an effective strategy to promote change and advocate for marginalized populations.Conclusion: Research-based theatre is an innovative approach which can be utilized to promote social accountability at regional medical campuses, advocating for the health needs of the communities in which they are located, with the added bonus of educating current and future health professionals.